The Effects of Prescribed Fire on Artificial Wild Turkey Nest Survival in Closed‐Canopy Mixed Hardwood Forest - Mariah G. McInnis; Robert A. Gitzen; Bret A. Collier; William D. Gulsby (Ecology and Evolution)
ABSTRACT The eastern wild turkey (Meleagris gallopavo) is an economically and culturally important upland game bird that has recently declined in abundance across portions of the Southeast. Prescribed fire can be used to improve vegetation conditions for wild turkey nesting and brooding, but there are concerns that the application of large‐scale prescribed fire can directly or indirectly impact turkey nest success. Therefore, there is a need to improve understanding of the effects of large‐scale burns on turkey reproduction, particularly how fire effects on vegetation might affect nest success rates. We implemented an artificial nest study on the Talladega National Forest in northeast Alabama, where prescribed fire is implemented across ≤ 8000 ha annually in large (> 300 ha) burn units. We monitored a total of 230 artificial turkey nests during April–May 2019 and 2020. Nests were systematically distributed throughout the study area at a density of 1 nest/202 ha in areas burned 1, 2, 3, 4, and 5–10 years prior to ensure proportional representation of time since fire. The overall artificial nest predation rate was 25%. Top predators included gray foxes (Urocyon cinereoargenteus; 10 nests), opossums (Didelphis virginiana; 9 nests), and coyotes (Canis latrans; 7 nests). We did not detect a relationship between time since fire (p > 0.05) or vegetation measurements (p > 0.05) and artificial nest predation. We believe the patterns we observed were explained by high overstory canopy cover (~90%) across the study area that limited vegetation response to fire. By mediating the potential effects of fire on understory vegetation structure, overstory canopy cover influences the degree to which fire alters concealment cover for nesting hens. Additional research is needed to determine whether large‐scale prescribed fire directly or indirectly affects wild turkey nest success in systems with lower canopy cover. Additionally, our study outlines evidence that vegetation responses to prescribed fire are site‐dependent.